PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL DARI TINDAKAN PASSING OFF BERDASARKAN UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK - Hendra, Rahmad; ', Samariadi; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Developments and advances in the field of economics, mainly trade in goods and services had a positive impact and negative for the world in the field of industrial intellectual property rights, especially in the field of trademark. The influx of economic globalization lead to diversity in the field of trademark infringement. Passing off action is a well-known mark piggybacking on actions carried out unlawfully, and result in unfair competition.The existence of Law Number 15 Year 2001 on trademark to this day can not provide legal certainty regarding passing off action as a violation of well-known mark. The purpose of this study is the first to determine the position of passing off action in violation of the act trademark in Indonesia, both know the legal protection of well-known mark of passing off action in Indonesia.Based on the research results of the problem formulation, it can be concluded that, first the act of passing off position in the legal system in Indonesia trademark infringement is included into the trademark, but the Act has not expressly mention. Second, concept of the protection of well-known mark of passing off action in the Indonesian legal system trademark consists of preventive measures and efforts repressive, preventive efforts made by the mechanism known brand registration, and legal socialization trademark. Repressive efforts to form a civil action and / or criminal prosecution in accordance with the provisions of the Trademark Law.Advice from the author, first namely law enforcement officers should have a strategic role in the field of legislation to renew the Trademark Act in order to provide legal certainty to the well-known mark infringement action including passing off. Second, should be legal protection trademark made in line with the oversight of all elements of law enforcement. Third, of Indonesia as a member of the WTO should be able to cope with unfair competition actions such as passing off by adjusting the rules of international conventions appropriate to the needs of the Republic of Indonesia.Key Words : Well-known Marks - Passing Off – Unfair Competition